Comparative study of the elimination of copper, cadmium, and methylene blue from water by adsorption on the citrus Sinensis peel and its activated carbon. Issue 17 (31st March 2022) - El Malti, Wassim; Hijazi, Akram; Khalil, Zahraa Abou; Yaghi, Zahraa; Medlej, Mohamad Kazem; Reda, Mohamad
Abstract : The accumulation of heavy metals and dyes in wastewater is a persistent environmental threat with serious hazards consequences affecting all living organisms. Citrus Sinensis peel and its activated carbon particles effectively remove Cu(ii ), Cd(ii ), and MB from water. Abstract : The accumulation of heavy metals and dyes in wastewater is a persistent environmental threat with serious hazards consequences affecting all living organisms. Their removal has become a challenging environmental requirement. Adsorption using agricultural waste is one of the cost-effective removal techniques in which the biomass can be valorized. In this study, two adsorbents were prepared and compared in removing copper, cadmium, and methylene blue from water: citrus Sinensis peel (CP) and its activated carbon (AC). Many physical and chemical properties of the prepared adsorbents were investigated using several techniques. Various operational parameters such as initial adsorbate concentration, contact time, pH, adsorbent mass, and temperature were examined. The optimum uptake of Cd, Cu, and MB was obtained after 2 h contact time by using 0.25 g of adsorbent and 400 mg L −1 metal ions or 100 mg L −1 MB initial concentration at pH 5 (for metal ions only) and temperature of 25 °C. Slight superiority for the CP was seen. Furthermore, isothermal models were resolved in all the studied cases. Unlike for MB, the Langmuir model is more applicable for the adsorption of the cations on both adsorbents with maximum adsorption of 80 mg g −1 of Cd(ii ) on CP. Finally, the adsorbents achieved good reuse performance, especially for CP which can be used up to 4 times to remove the metal ions, proving that they are low-cost and environmentally friendly materials able to remove inorganic and organic contaminants from water.